Rotator cuff tears reparability index based on pre-operative MRI: our experience - Di Benedetto, Paolo; Beltrame, Alessandro; Cicuto, C; Battistella, C; Gisonni, Renato; Cainero, Vanni; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: It is recognised that a significant percetage of large and massive rotator cuff tears (RCT) cannot be anatomically repaired and this correlates with a worste outcome in terms of pain, active range of motion, increased incidence of retair. The aim of our work is to find reliable index on preoperative MRI shoulder image to assist orthopaedist in surgical planning of rotatator cuff tears repair. Methods: We performed a retrospective study on a population on 131 patients undergoing arthroscopic cuff repair by a single expert surgeon. Pre-operative MRI images were evaluated by a single orthopaedist, trained on MRI shoulder images ad blinded to surgical outcome. For each magnetic resonance we evaluated the following 9 parameters: fatty Infiltration (FI), Patte Stage (PS), tear size measured in medial-lateral (ML) and anterior- posterior (AP) dimension, Tangent Sign (TS), Occupation Grade (OG), Acromion-Humeral Distance (AHD), Inferior Gleno-Humeral Distance (IGHD), Glenoid Version Angle (GVA). We divided population into two groups: patients who obtained a complete repair of RCT (n=110) and patients who obtained only a partial repair of RCT (n=21). For each MRI index we conducted statistical analysis (Student’s t test, Mann- Whitney U test, Shapiro-Wilk test, Chi-square test, Fisher exact test, ROC curves and maximum Youden index) to find a Cut Off value useful to predict partial repair. Results: We have found statistical significance in predicting partial repair on MRI mesurements of Fatty Infiltration (FI grade ≥3; test di Fisher p<0.001), Patte Stage (grade= 3; test di Fisher p<0.001), Tear size measured in ML (>36 mm; Mann-Whitney p<0.001), Positive Tangent Sign (Chi-quadro p<0.001; sensitivity 95,3%, specificity 83,6%), Occupation Grade (OG <0,46; t-test p<0.001). Acromion-Humeral Distance (AHD <7 mm), Inferior Gleno-Humeral Distance (IGHD >5 mm). Tear size measured in AP (>21 mm; Mann-Whitney p<0.001) seems to be dependent on the contextual size of the lesion in ML. We haven’t found statistical significance in predicting partial repair of Glenoid Version Angle. Conclusions: A systematic observation of seven independent MRI parameters (FI, PS, tear size ML, TS, OG, AHD, IGHD) can help the surgeon to predict the impossibility to obtain complete repair of RCT and to consider different surgical approach.